Arabidopsis PARC6 Is Critical for Plastid Morphogenesis in Pavement, Trichome, and Guard Cells in Leaf Epidermis - Ishikawa, Hiroki; Yasuzawa, Mana; Koike, Nana; Sanjaya, Alvin; Moriyama, Shota; Nishizawa, Aya; Matsuoka, Kanae; Sasaki, Shun; Kazama, Yusuke; Hayashi, Yoriko; Abe, Tomoko; Fujiwara, Makoto T.; et al. (Frontiers in Plant Science, 2020)
Recently, a recessive Arabidopsis thaliana mutant with abundant stromules in leaf epidermal pavement cells was visually screened and isolated. The gene responsible for this mutant phenotype was identified as PARC6, a chloroplast division site regulator gene. The mutant allele parc6-5 carried two point mutations (G62R and W700stop) at the N- and C-terminal ends of the coding sequence, respectively. Here, we further characterized parc6-5 and other parc6 mutant alleles, and showed that PARC6 plays a critical role in plastid morphogenesis in all cell types of the leaf epidermis: pavement cells, trichome cells, and guard cells. Transient expression of PARC6 transit peptide (TP) fused to the green fluorescent protein (GFP) in plant cells showed that the G62R mutation has no or little effect on the TP activity of the PARC6 N-terminal region. Then, plastid morphology was microscopically analyzed in the leaf epidermis of wild-type (WT) and parc6 mutants (parc6-1, parc6-3, parc6-4 and parc6-5) with the aid of stroma-targeted fluorescent proteins. In parc6 pavement cells, plastids often assumed aberrant grape-like morphology, similar to those in severe plastid division mutants, atminE1 and arc6. In parc6 trichome cells, plastids exhibited extreme grape-like aggregations, without the production of giant plastids (>6 µm diameter), as a general phenotype. In parc6 guard cells, plastids exhibited a variety of abnormal phenotypes, including reduced number, enlarged size, and activated stromules, similar to those in atminE1 and arc6 guard cells. Nevertheless, unlike atminE1 and arc6, parc6 exhibited a low number of mini-chloroplasts (<2 µm diameter) and rarely produced chloroplast-deficient guard cells. Importantly, unlike parc6, the chloroplast division site mutant arc11 exhibited WT-like plastid phenotypes in trichome and guard cells. Finally, observation of parc6 complementation lines expressing a functional PARC6-GFP protein indicated that PARC6-GFP formed a ring-like structure in both constricting and non-constricting chloroplasts, and that PARC6 dynamically changes its configuration during the process of chloroplast division.